Epidemiology of foot‐and‐mouth disease outbreaks in Thailand from 2011 to 2018. Issue 6 (22nd November 2022) - Chanchaidechachai, Thanicha; Saatkamp, Helmut; de Jong, Mart; Inchaisri, Chaidate; Hogeveen, Henk; Premashthira, Sith; Buamitoup, Noppawan; Prakotcheo, Rotchana; van den Borne, Bart H. P.
Abstract: Foot‐and‐mouth disease (FMD) is one of the most important animal diseases hindering livestock production in Thailand. In this study, a temporal and spatial analysis at the subdistrict level was performed on FMD outbreak reports in Thailand from 2011 to 2018. Risk factors associated with FMD outbreaks were furthermore investigated using generalized estimating equations. The results showed that the incidence of FMD outbreaks was the highest in 2016 and was affected by season, with a peak in FMD outbreaks occurring in the rainy‐winter season, during October to December. FMD outbreaks were mostly distributed in small clusters within a few subdistricts. Some high‐risk areas with repeated outbreaks were detected in the central regions. Risk factors, including the increase of subdistrict's size of the dairy population, beef population or pig population, the low percentage of forest area, subdistricts in the provinces adjacent to Malaysia, the presence of a livestock market and the occurrence of an FMD outbreak in a neighbouring subdistrict in the previous month significantly increased the odds of having an FMD outbreak. The increase in proximity to the nearest subdistrict with an FMD outbreak in the previous month decreased the odds of having FMD outbreaks. This study helped to identify high‐risk areas and periods of FMD outbreaks in Thailand. Together with the identified risk factors, its results can be used to optimize the FMD control programme in Thailand and in other countries having a similar livestock industry and FMD situation.